System Informasi Resto Kuru Yuk Chicken Berbasis Online Untuk Pemesanan Makanan Dan Minuman - Samodra Anugrah, Syawal; Suarna, Nana; Dwilestari , Gifthera (PT. Bangun Harapan Bangsa, 2023)
KuRuyuk Resto is a social interaction center where people can gather, talk, write, read, discuss or just pass the time. To realize customer satisfaction, Resto KuRuyuk must have a good ordering system to increase revenue. The research method used is to use data collection methods starting from observation, interviews, and literature study. As for software development through the R&D approach. The problem with KuRuyuk Resto is having difficulties in serving orders, still using manual recording and not yet computerized or still using conventional recording. The purpose of this research is to improve customer service and satisfaction in ordering food and beverages. The results of this study are that it can facilitate service and the effectiveness of workers' time becomes faster and more efficient. And can produce information quickly, precisely and accurately. After testing with SUS (System Usability Scale) an accuracy value of 76% was obtained. Keywords: Information system, restaurant, improvement, sales, online based